The Influence Of Stad And Inquiry Type Cooperative Learning Models On The Smash Volleyball Skills Of Students Of Takalar 1st High School - Azis, Ilham; Sudirman, sudirman (ILIN Education Indonesia, 2024)
This research is experimental research. The aim of this research is to determine the influence of the Tsad Type Cooperative Learning Model on the Volleyball Smash Skills of Students at SMA Negeri 1 Takalar. This type of research is Quasi Experimental Design or Posttest-only control design. The population of this study were class data analysis, this research concludes that there is a significant influence of the STAD type cooperative learning model on volleyball smash skills with a t=count value of 18.531 > t=table 2.042 and the results are sig. (2-tailed) namely 0.000 < 0.05, there is a significant influence of the inquiry model on volleyball smash skills with a t=count value of 18.531 > t=table 2.042 and the results are sig. (2-tailed), namely 0.000 < 0.05, there is a significant difference in the influence of the STAD type cooperative learning model on volleyball smash skills with an average value of 16.03 and the inquiry model with an average value of 14.33, the value t= calculated is 2.502 > t=table 2.042 with a significant value of 0.015<0.05 for students of SMA Negeri 1 Takalar.